PENERAPAN TERAPI BERMAIN PUZZLE UNTUK MENGATASI TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) SAAT HOSPITALISASI - Anisha, Nurul; Lestari, Raja Fitrina (Coping: Community of Publishing in Nursing, 2022)
Hospitalization is a planned or emergency process that requires children to undergo treatment in a hospital and undergo a therapy program until they are discharged back. The hospitalization process can have an impact on children's anxiety. Anxiety in children can be overcome by channeling feelings of anxiety towards a fun play activity, so that it is expected to support the healing process and be cooperative in every nursing action. Puzzle play therapy is one of the play therapies that can be given to preschool-aged children while undergoing hospitalization. Through puzzle play activities, it is hoped that it can provide a sense of pleasure and be an effective way to forget for a moment the anxiety in children. The purpose of implementing evidence-based nursing practice is to overcome anxiety in preschool-aged children during hospitalization. The type of research conducted is descriptive research with a case study approach to describe the application of puzzle play therapy to anxiety in pediatric nursing care with hospitalization. The instruments used in this case study are observation sheets and facial image scale (FIS) anxiety measuring instruments. From the results of the application that has been carried out by providing puzzle play therapy interventions to children who experience anxiety in the Edelweiss children's inpatient room at Arifin Achmad Hospital, Riau Province, it was found that the child's anxiety decreased from severe anxiety to not anxious in the first patient, while in the second patient Anxiety decreased from moderate anxiety to non-anxiety.